The potential value of LC-MS non-targeted metabonomics in the diagnosis of follicular thyroid carcinoma - Qin, Jiali; Yang, Yang; Du, Wei; Li, Gang; Wu, Yao; Luo, Ruihua; Liu, Shanting; Fan, Jie (Frontiers in Oncology, 2022)
Background:To explore the metabolic differences of follicular thyroid carcinoma (FTC) by metabonomics, to find potential biomarkers for the diagnosis of FTC, and to explore the pathogenesis and diagnosis and treatment strategies of FTC. Methods：The metabonomics of 15 patients with FTC and 15 patients with follicular thyroid nodules(FTN) treated in Henan Cancer Hospital were analyzed by liquid chromatography-mass spectrometry (LC-MS). Results:The analysis showed that the metabolite profiles of FTC tissues could be well distinguished from those of control tissues, and 6 kinds of lipids were identified respectively, including lysophosphatidic acid(LysoPA) (LysoPA(0:0/18:0),LysoPA(0:0/18:2(9Z,12Z)),LysoPA(20:4(8Z,11Z,14Z,17Z)/0:0)); phosphatidic acid(PA) (PA(20:3(8Z,11Z,14Z)/0:0),PA(20:4(5Z,8Z,11Z,14Z)/0:0),PA(20:5(5Z,8Z,11Z,14Z,17Z)/0:0)); lysophosphatidylcholine(LPC) (LPC(18:1),LPC(16:0),LPC(16:1(9Z)/0:0),LPC(17:0),LPC(22:4(7Z,10Z,13Z,16Z),LPC(20:2(11Z,14Z)); phosphatidylcholine(PC)（PC(14:0/0:0),PC(16:0/0:0); sphingomyelin(SM) (d18:0/12:0); fatty acid(FA)(18:1(OH3)). There are 2 kinds of amino acids, including L-glutamate,L-glutamine.There are 3 other metabolites, including retinol,flavin adenine dinucleotide,androsterone glucuronide.Lipid metabolites are the main metabolites in these metabolites.The metabolic pathways related to FTC were analyzed by KEGG and HMDB, and 9 metabolic pathways were found, including 4 amino acid related metabolic pathways, 1 lipid metabolic pathways and 4 other related pathways. Conclusions：There are significant differences in many metabonomic characteristics between FTC and FTN, suggesting that these metabolites can be used as potential biomarkers. Further study found that LysoPA and its analogues can be used as biomarkers in the early diagnosis of FTC.It may be related to the abnormal metabolism of phospholipase D (PLD), the key enzyme of LysoPA synthesis caused by RAS pathway. At the same time, it was found that the metabolic pathway of amino acids and lipids was the main metabolic pathway of FTC. The abnormality of LysoPA may be the cause of follicular tumor carcinogenesis caused by lipid metabolic pathway.